Microbiological Quality of Different Bottled Water Brands, Marketed in Trabzon, Turkey - Dalman, Omer; Varer Kutanis, Vildan; Col, Melek (Asian Journal of Chemistry, 2012)
The microbiological quality of demijohn (19 L) and disposable bottled water products of six different brands were tested with membrane filter technique over a period of 6 months. Bacteriological quality of some of the demijohn bottled water samples was investigated after exposure to the sun light. Under this conditions, microbial contamination was mostly seen in the samples marked as C and E in terms of total coliforms and heterotrophic plate counts. Although their shelf-live was determined as one year, only the second sample (B) was evaluated as appropriate to standards determined by regulation on Intended Human Water Consumption and World Health Organization for 6 months. C and E were not consistent with standards beginning from 1st month. Eventually, in performed study, most of the samples tested were unsuitable for drinking purpose according to permitted levels, if they were consumed even a month after the date of manufacturing. Although, same investigations done for disposable bottled water disclosed that, such as packaged waters safer than the water in demijohn. Because, it was determined that 97 % of 36 tested water samples were found to appropriate to standards.